PENGARUH KONDISI KEUANGAN PERUSAHAAN, UKURAN PERUSAHAAN, OPINION SHOPPING DAN AUDIT CLIENT TENURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014 – 2017 - Anggia Maharani, 15.05.52.0274; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2019)
This study aims to examine financial condition, company size, opinion shopping and audit client tenure that influence the acceptance going concern of audit opinion in manufacturing companies listed on the Indonesia stock exchange for the period 2014-2017. The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2014-2017 period. The sample selection uses the purpose sampling method. Total of sample in this research is 66 data. The analytical tool used in this study is logistic regression analysis. The test results show that financial conditon has a significant negative effect on the acceptance going concern of audit opinion. Company Size, Opinion shopping and Audit Client Tenure do not have a significant effect on the acceptance going concern of audit opinion.